Healthy lifestyles and nutrition to students in the fifth year of secondary school, Colegio José Antonio Encinas, Juliaca - 2013 - Chalco Quispe, Ginna Yohanna (2019)
Objective: To determine the existence of relationship between healthy lifestyles and nutritional status of studentsenrolled in the fifth year of secondary education. Methods: We performed to transeccional experimental,correlational, was conducted with a sample of 176 students enrolled in the fifth year of secondary education.The instrument was the questionnaire profile lifestyle (PEPS-I) the Nola Pender which consisted of questionsof 6 dimensions: nutrition, exercise, health responsibility, stress management, interpersonal support and selfactualization; nutritional status for BMI (Body Mass Index) was used. Results: 64.2% of students presenteda normal nutritional status, followed by 21.0% who were overweight and 14.8% were malnourished; 57.5%also showed a state of life in the healthy range, 23.3% unhealthy style of life and 19.3% of students had a veryhealthy lifestyle. Conclusions: There relationship between lifestyle and nutritional status in six dimensions witha (sig=.000).